Method for preparing sulfide polymer composite solid electrolyte membrane through one-pot ball milling method and application of sulfide polymer composite solid electrolyte membrane

By combining Li4SnS4 and PEO in a specific proportion and using a one-pot ball milling method to prepare a sulfide polymer composite solid electrolyte membrane, the problems of air stability and low ionic conductivity of sulfide electrolyte in lithium-ion batteries are solved, and high efficiency is achieved. Low impedance electrolyte performance, suitable for all solid state lithium batteries.

CN119170884APending Publication Date: 2024-12-20ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411422934.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the air stability and low ionic conductivity of sulfide solid electrolytes lead to safety hazards and insufficient performance. A single sulfide or polymer electrolyte cannot meet the application and industrialization requirements, and the traditional preparation process is inefficient.

Method used

The two solid electrolytes of Li4SnS4 and PEO are combined in a specific proportion, and the composite slurry is efficiently and quickly prepared by a one-pot ball milling method to obtain a sulfide polymer composite solid electrolyte membrane with low interfacial impedance and high ionic conductivity.

Benefits of technology

It improves the transmission capacity and ionic conductivity of lithium ions, reduces the interface impedance, solves the defects of a single electrolyte, and is suitable for all-solid lithium batteries, with high preparation efficiency and adjustable film thickness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170884A_ABST
    Figure CN119170884A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium batteries, and discloses a method for preparing a sulfide polymer composite solid electrolyte membrane through a one-pot ball milling method and application of the sulfide polymer composite solid electrolyte membrane. Two solid electrolytes Li4SnS4 and PEO are combined according to a specific ratio, and the composite slurry is efficiently and rapidly prepared by adopting a one-pot ball milling method of a specific process, so that the composite solid electrolyte membrane is finally obtained. According to the method, the preparation efficiency is high, the thickness of the composite membrane is adjustable, and the obtained sulfide polymer composite solid-state electrolyte membrane has relatively low interface impedance and relatively high ionic conductivity, so that the sulfide polymer composite solid-state electrolyte membrane can be better applied to an all-solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a method for preparing a sulfide polymer composite solid electrolyte membrane by a one-pot ball milling method and an application thereof. Background Art

[0002] Lithium-ion batteries have made remarkable achievements in the field of commercialization, but the current commercial lithium-ion batteries using flammable organic electrolytes have safety risks, low energy density and short cycle life. In order to meet the needs of the new energy vehicle and energy storage market, it is crucial to develop safe, high energy density and long cycle life lithium-ion batteries. Replacing liquid organic electrolytes with solid electrolytes and developing all-solid-state lithium batteries is an important way.

[0003] Solid electrolyte is one of the most critical components in all-solid-state lithium batteries. The quality of the electrolyte directly affects the performance of all-solid-state lithium batteries. Solid electrolytes can be divided into inorganic electrolytes and polymer electrolytes according to their composition. Among them, inorganic electrolytes include oxides, sulfides, halides, etc.

[0004] Among all types of solid electrolytes, sulfide solid electrolytes have high room temperature ionic conductivity and good mechanical properties, but their poor air stability leads to the production of toxic hydrogen sulfide (H2S), structural damage and performance degradation, which hinders the large-scale application of sulfide solid electrolytes. Compared with sulfur-phosphate-based solid electrolytes, the sulfide solid electrolyte Li4SnS4 produces relatively less H2S. However, the ionic conductivity of Li4SnS4 only reaches 7.0×10 -5 S cm -1 , the low conductivity makes it difficult to be used in all-solid-state lithium batteries. The present invention finds that this is due to the strong rigidity and brittle fracture characteristics of the inorganic solid electrolyte, which leads to large interface impedance and extremely poor solid-solid interface contact.

[0005] The flexibility of PEO polymer solid electrolyte can fit well with electrode materials, effectively solve the interface contact problem, and can be mass-produced to adapt to various required shapes and sizes. However, due to its low mechanical strength and poor mechanical properties, there is a risk of being pierced after the formation of lithium dendrites. At the same time, PEO also has disadvantages such as low ionic conductivity.

[0006] In short, neither single sulfide electrolyte nor polymer electrolyte can meet the requirements of application and industrialization. In addition, the traditional preparation of polymer uniform slurry mainly relies on heating and stirring process, which usually takes a long time, increases energy consumption and reduces production efficiency. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a preparation method of a sulfide polymer composite solid electrolyte membrane by a one-pot ball milling method and its application. The present invention combines two solid electrolytes, Li4SnS4 and PEO, in a specific ratio, and uses a one-pot ball milling method with a specific process to efficiently and quickly prepare a composite slurry, and finally obtain a composite solid electrolyte membrane. The method of the present invention not only has high preparation efficiency and adjustable composite membrane thickness, but also the obtained sulfide polymer composite solid electrolyte membrane has lower interface impedance and higher ionic conductivity, so it can be better applied to all-solid-state lithium batteries.

[0008] The specific technical scheme of the present invention is:

[0009] In a first aspect, the present invention provides a method for preparing a sulfide polymer composite solid electrolyte membrane by a one-pot ball milling method, comprising the following steps:

[0010] (1) Li4SnS4, polyethylene oxide, lithium salt, solvent and ball milling beads are placed in an inert atmosphere and sealed.

[0011] The mass ratio of Li4SnS4 to polyethylene oxide is 1:5-20; the mass ratio of ball milling beads to polyethylene oxide is 20-80:1;

[0012] (2) The sealed ball mill jar is placed in a ball mill and subjected to one-step ball milling to obtain a uniform composite slurry.

[0013] (3) The composite slurry is coated on a substrate to obtain a composite solid electrolyte slurry layer with uniform thickness.

[0014] (4) The composite solid electrolyte slurry layer is first air-dried and then vacuum-dried to obtain a sulfide polymer composite solid electrolyte membrane.

[0015] As described in the background of this application, a single Li4SnS4 solid electrolyte has the characteristics of strong rigidity and easy brittle fracture, which makes its interface impedance large and the solid-solid interface contact extremely poor, ultimately resulting in low ion conductivity. Although a single PEO polymer solid electrolyte has better flexibility and can effectively solve the interface contact problem, it has a low mechanical strength and a risk of being pierced after the formation of lithium dendrites. At the same time, it also has the disadvantage of low ion conductivity.

[0016] To this end, the present invention attempts to compound the above two solid electrolytes in order to obtain a composite solid electrolyte with lower interface impedance and higher ionic conductivity. However, the present invention found in the research process that it is not possible to obtain ideal performance simply by compounding Li4SnS4 with polyethylene oxide. The present invention found that only after compounding Li4SnS4 with polyethylene oxide in a specific ratio and adopting a special ball milling process, the final composite solid electrolyte has lower interface impedance and higher ionic conductivity.

[0017] In summary, the present invention combines two solid electrolytes, Li4SnS4 and polyethylene oxide (PEO), and uses a one-pot ball milling method with a specific process to efficiently and quickly prepare a composite slurry, and finally obtain a composite solid electrolyte membrane. In the composite solid electrolyte membrane obtained by the present invention, PEO is used as a substrate, and the doping of an appropriate amount of Li4SnS4 solid electrolyte reduces the crystallinity of the PEO polymer base and increases the number of molecular chains in the amorphous region, thereby helping to improve the transmission capacity of Li ions and enhance ionic conductivity, thereby solving the defects of low ionic conductivity of Li4SnS4 and PEO itself. Finally, the composite solid electrolyte membrane of the present invention has lower interface impedance and higher ionic conductivity, so it can be better applied to all-solid-state lithium batteries.

[0018] Preferably, in step (1), the lithium salt is LiTFSi.

[0019] Preferably, in step (1), the solvent is acetonitrile (ACN), tetrahydrofuran (THF) or acetone (AC).

[0020] Preferably, in step (1), the mass ratio of Li4SnS4 to polyethylene oxide is 1:10-20.

[0021] Preferably, in step (2), the rotation speed of the ball mill is 200-600 rpm, and the ball milling time is 60-180 min.

[0022] Preferably, in step (3), the substrate is made of glass, polytetrafluoroethylene (PTFE), release paper or polyethylene terephthalate (PET).

[0023] Preferably, in step (3), the coating thickness is 100-300 μm.

[0024] Preferably, in step (4), the vacuum drying is carried out at a temperature of 50-80°C and for a time of 12-48 hours.

[0025] In a second aspect, the present invention provides the use of the sulfide polymer composite solid electrolyte membrane obtained by the above preparation method in an all-solid-state lithium battery.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] (1) The present invention combines two solid electrolytes, Li4SnS4 and PEO, in a specific ratio, and uses a one-pot ball milling method with a specific process to efficiently and quickly prepare a composite slurry, and finally obtain a composite solid electrolyte membrane. The sulfide polymer composite solid electrolyte membrane obtained by the method of the present invention has lower interface impedance and higher ion conductivity, and can therefore be better applied to all-solid-state lithium batteries.

[0028] (2) According to the specific method of the present invention, an active filler Li4SnS4 solid electrolyte is added to the PEO polymer matrix. After compounding, the active filler not only reduces the crystallinity of the PEO polymer matrix, but also increases the number of molecular chains in the amorphous region, thereby helping to improve the Li ion transmission capacity and enhance the ionic conductivity, thereby solving the defect of low ionic conductivity of Li4SnS4 and PEO itself.

[0029] In summary, the present invention combines two solid electrolytes, Li4SnS4 and polyethylene oxide (PEO), and uses a one-pot ball milling method with a specific process to efficiently and quickly prepare a composite slurry, and finally obtain a composite solid electrolyte membrane. In the composite solid electrolyte membrane obtained by the present invention, PEO is used as a substrate, and the doping of an appropriate amount of Li4SnS4 solid electrolyte reduces the crystallinity of the PEO polymer base and increases the number of molecular chains in the amorphous region, thereby helping to improve the transmission capacity of Li ions and enhance ionic conductivity, thereby solving the defects of low ionic conductivity of Li4SnS4 and PEO itself. Finally, the composite solid electrolyte membrane of the present invention has lower interface impedance and higher ionic conductivity, so it can be better applied to all-solid-state lithium batteries.

[0030] (3) The method of the present invention has high preparation efficiency and adjustable composite film thickness, and is suitable for planned promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the X-ray diffraction pattern of the composite solid electrolyte membrane prepared in Example 1;

[0032] Figure 2 is a scanning electron microscope (SEM) image of the composite solid electrolyte membrane prepared in Example 1;

[0033] Figure 3 The impedance diagram of the composite solid electrolyte membrane prepared in Example 1 at 30°C;

[0034] Figure 4 This is a cycle performance diagram of the composite solid electrolyte membrane prepared in Example 1;

[0035] Figure 5The impedance diagram of the composite solid electrolyte membrane prepared in Example 3 at 30°C;

[0036] Figure 6 This is a scanning electron microscope image of the composite solid electrolyte membrane prepared in Comparative Example 1;

[0037] Figure 7 This is the X-ray diffraction pattern of the composite solid electrolyte membrane prepared in Comparative Example 2. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the embodiments.

[0039] Example 1

[0040] (1) 0.06 g Li4SnS4 solid electrolyte, 0.60 g PEO polymer, 0.244 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 40:1, and the jar was sealed;

[0041] (2) placing the ball milling jar of step (1) into a ball mill and performing one-step ball milling at a speed of 400 rpm for 120 min to obtain a uniform composite slurry;

[0042] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 200 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0043] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a vacuum oven at 60° C. and dried for 24 h to finally obtain a composite solid electrolyte membrane.

[0044] Example 2

[0045] (1) 0.03 g Li4SnS4 solid electrolyte, 0.60 g PEO polymer, 0.244 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 40:1, and the jar was sealed;

[0046] (2) placing the ball milling jar of step (1) into a ball mill and performing one-step ball milling at a speed of 300 rpm for 180 min to obtain a uniform composite slurry;

[0047] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 100 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0048] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a 60° C. vacuum oven for drying for 48 h, thereby finally obtaining a composite solid electrolyte membrane.

[0049] Example 3

[0050] (1) 0.09 g Li4SnS4 solid electrolyte, 0.60 g PEO polymer, 0.196 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 20:1, and the jar was sealed;

[0051] (2) placing the ball milling jar of step (1) into a ball mill and performing one-step ball milling at a speed of 200 rpm for 120 min to obtain a uniform composite slurry;

[0052] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 100 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0053] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a vacuum oven at 60° C. and dried for 24 h to finally obtain a composite solid electrolyte membrane.

[0054] Example 4

[0055] (1) 0.12 g Li4SnS4 solid electrolyte, 0.60 g PEO polymer, 0.244 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 60:1, and the jar was sealed;

[0056] (2) placing the ball milling jar of step (1) into a ball mill and performing one-step ball milling at a speed of 500 rpm for 120 min to obtain a uniform composite slurry;

[0057] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 200 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0058] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a vacuum oven at 60° C. and dried for 36 hours to finally obtain a composite solid electrolyte membrane.

[0059] Example 5

[0060] (1) 0.06 g Li4SnS4 solid electrolyte, 0.60 g PEO polymer, 0.244 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 80:1, and the jar was sealed;

[0061] (2) placing the ball milling jar of step (1) into a ball mill and performing one-step ball milling at a speed of 600 rpm for 120 min to obtain a uniform composite slurry;

[0062] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 300 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0063] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a vacuum oven at 60° C. and dried for 12 h to finally obtain a composite solid electrolyte membrane.

[0064] Comparative Example 1 (Compared with Example 1: lower spherical mass ratio)

[0065] (1) 0.06 g Li4SnS4 solid electrolyte, 0.60 g PEO polymer, 0.244 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 15:1, and the jar was sealed;

[0066] (2) placing the ball milling jar prepared in step (1) into a ball mill and performing one-step ball milling at a speed of 400 rpm for 120 min to obtain a composite slurry;

[0067] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 200 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0068] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a vacuum oven at 60° C. and dried for 24 h to finally obtain a composite solid electrolyte membrane.

[0069] Comparative Example 2 (Compared with Example 1: No Li4SnS4 solid electrolyte is added)

[0070] (1) 0.60 g PEO polymer, 0.244 g LiTFSi and 12 ml acetonitrile were added to a zirconium dioxide ball milling jar, and zirconium dioxide ball milling beads were added, wherein the ball-to-mass ratio was 40:1, and the jar was sealed;

[0071] (2) placing the ball milling jar of step (1) into a ball mill and performing one-step ball milling at a speed of 400 rpm for 120 min to obtain a uniform composite slurry;

[0072] (3) pouring the composite slurry obtained in step (2) onto release paper, setting the coater height to 200 μm, and coating to obtain a composite solid electrolyte slurry with uniform thickness;

[0073] (4) The composite solid electrolyte slurry obtained in step (3) was allowed to stand and dry, and then transferred to a vacuum oven at 60° C. and dried for 24 h to finally obtain a composite solid electrolyte membrane.

[0074] Performance Testing

[0075] The composite solid electrolyte membranes prepared in each embodiment and each comparative example were punched to obtain discs with a diameter of 16 mm, and assembled into a pair of blocking cells to test electrochemical impedance, wherein the counter electrode was stainless steel. The ionic conductivity of the electrolyte was tested in an environment of 30°C. The ionic conductivity calculation formula is: σ = L / SR, unit is S cm -1 , where L is the thickness of the solid electrolyte membrane, S is the area of ​​the stainless steel, and R is the impedance value obtained by the test. The full battery was assembled for charge and discharge cycle testing, where the positive electrode was lithium iron phosphate and the negative electrode was lithium metal. Cycling at 0.1C, voltage range 2.5-3.8V, theoretical capacity 170mAh g -1 Preparation of positive electrode: Lithium iron phosphate, conductive agent Super P, binder polyvinylidene fluoride are mixed with solvent N-methylpyrrolidone in a mass ratio of 7:2:1 to make a homogeneous slurry, which is applied on the aluminum current collector. After drying, it is punched into discs with a diameter of 12 mm as the positive electrode.

[0076] Figure 1 The XRD of the composite solid electrolyte prepared in Example 1 shows that Example 1 is mainly a PEO polymer phase (PDF#50-2158).

[0077] Figure 2 This is a SEM image of the surface of the prepared composite solid electrolyte membrane. The surface is flat, with a small amount of nano-scale particles exposed on the surface and evenly dispersed, indicating that the components of the prepared composite solid electrolyte are uniform.

[0078] Figure 3 The impedance diagram of the composite solid electrolyte prepared in Example 1 has a total impedance value of 153Ω, which has good interface wettability.

[0079] Figure 4 The cycle performance diagram of the composite solid electrolyte membrane prepared in Example 1 shows that the initial discharge capacity is 141 mAh g at a rate of 0.1C. -1 The discharge capacity after 65 cycles is 122.1 mAh g -1 , the coulombic efficiency always remained above 95%, and the capacity retention rate was 86.4%, indicating that the material assembled using the composite solid electrolyte membrane has excellent cycle stability.

[0080] Figure 5The impedance diagram of the composite solid electrolyte membrane prepared in Example 3 at 30° C. has a total impedance value of 600Ω, which is significantly larger than that in Example 1.

[0081] Figure 6 This is a scanning electron microscope image of the composite solid electrolyte membrane prepared in Comparative Example 1. It can be seen that there are a large number of particle agglomerates on the surface, indicating that Example 1 improves the ball-to-mass ratio to make ball milling more complete and more efficient, which can further reduce the occurrence of Li4SnS4 solid electrolyte agglomeration and make the distribution of various components in the composite solid electrolyte more uniform.

[0082] Figure 7 The X-ray diffraction pattern of the pure PEO-based solid electrolyte membrane prepared in Comparative Example 2 is Figure 1 In comparison, the intensity of the characteristic peak is higher, indicating that the addition of Li4SnS4 solid electrolyte reduces the crystallinity of the PEO polymer matrix and increases the number of molecular chains in the amorphous region, which helps to improve the Li ion transport capacity and enhance the ionic conductivity.

[0083] The ionic conductivity of the composite solid electrolyte prepared in each embodiment and each comparative example, as well as the initial specific capacity and capacity retention rate at a rate of 0.1C, are shown in Table 1:

[0084] Table 1

[0085]

[0086] As shown in Table 1, the sulfide polymer composite membrane prepared by the one-pot ball milling method in Example 1 has the best electrochemical properties. In the preparation process, too much or too little addition of Li4SnS4 solid electrolyte will affect its electrochemical properties. When the ball-to-mass ratio, ball milling time and rotation speed are not appropriate during the preparation of the precursor slurry, the obtained composite slurry is not uniform enough, which will affect the uniformity of the final composite solid electrolyte membrane, thereby affecting the electrochemical properties.

[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a sulfide polymer composite solid electrolyte membrane by a one-pot ball milling method, characterized in that The following steps are involved: (1) Li4SnS4, polyethylene oxide, lithium salt, solvent and ball milling beads are placed in a ball milling jar in an inert atmosphere and sealed; The mass ratio of Li4SnS4 to polyethylene oxide is 1:5-20; the mass ratio of ball milling beads to polyethylene oxide is 20-80:1; (2) placing the sealed ball mill jar in a ball mill and performing one-step ball milling to obtain a uniform composite slurry; (3) coating the composite slurry on a substrate to obtain a composite solid electrolyte slurry layer with uniform thickness; (4) The composite solid electrolyte slurry layer is first air-dried and then vacuum-dried to obtain a sulfide polymer composite solid electrolyte membrane.

2. The preparation method according to claim 1, characterized in that: In step (1), the lithium salt is LiTFSi.

3. The preparation method according to claim 1, characterized in that: In step (1), the solvent is acetonitrile, tetrahydrofuran or acetone.

4. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of Li4SnS4 to polyethylene oxide is 1:10-20.

5. The preparation method according to claim 1, characterized in that: In step (2), the rotation speed of the ball mill is 200-600 rpm, and the ball milling time is 60-180 min.

6. The preparation method according to claim 1, characterized in that: In step (3), the material of the substrate is glass, polytetrafluoroethylene, release paper or polyethylene terephthalate.

7. The preparation method according to claim 1, characterized in that: In step (3), the coating thickness is 100-300 μm.

8. The preparation method according to claim 1, characterized in that: In step (4), the vacuum drying temperature is 50-80°C and the time is 12-48h.

9. The sulfide polymer composite solid electrolyte membrane obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the sulfide polymer composite solid electrolyte membrane obtained by the preparation method according to any one of claims 1 to 8 or the sulfide polymer composite solid electrolyte membrane according to claim 9 in an all-solid-state lithium battery.

Citation Information

Cited By

  • Organic sulfide-polymer composite solid electrolyte and preparation method and application thereof

    CN122202487A